Legitimacy of collaborative environmental governance in New Zealand : the Manawatū River Leaders' Forum : a thesis presented in partial fulfilment of the requirements for the degree of Master in Environmental Management at Massey University, Manawatū, New Zealand - Naovalat, Souphamith (Massey University, 2015)
Over the past few decades, collaborative governance has emerged as an alternative to traditionally adversarial approaches such as hierarchical command-and-control regulation. A wide range of governance theory praises collaborative governance with multi-stakeholders’ participation as an effective strategy to deal with a public issue. Environmental deterioration, such as water pollution, is a cross-cutting issue that has been in a favour of collaborative approaches to resolve. The promise of collaborative environmental governance is to make environmental policy more effective for sustainability. However, multi-stakeholders’ participation poses challenges in practice if it really makes any difference to and is compatible with environmental policy decision-making processes within a set timeframe. Power imbalance, for example, entails legitimacy deficits to ensure the effectiveness of collaborative environmental governance. Therefore, legitimacy is an important concept that defines a political acceptance whether or to what extent collaborative governance can result in more sustainable or effective environmental policy. This study assesses legitimacy of collaborative environmental governance by using the Manawatu River Leaders’ Forum (MRLF), a collaborative forum to solve water quality issue in southern North Island of New Zealand, as a case study. The study focuses on developing a framework for assessing legitimacy based on three types of legitimacy including input, output and throughput legitimacy that are applicable to explore the MRLF’s effectiveness. In corresponding to these legitimacy types, the legitimacy assessment framework is designed with three dimensional factors including participatory quality, policy effectiveness and collaborative process with their own indicators and criteria. Results of analysing published data indicate that the MRLF is basically legitimated as a fundamental commencement for collaboration as participations by different stakeholders are active and collective decisions have been implemented. However, interviews with MRLF’s key stakeholders demonstrate different perspectives on legitimacy through an existing conflict. Through the three dimensional factors, governmental stakeholders perceive high legitimacy, while most non-governmental stakeholders perceive low legitimacy. This study suggests ways to look conflict as a collaborative learning, rather than fighting, to bridge a synergy between collaboration and conflict. Although collaboration aims to resolve conflicts, collaboration should be learnt as one aspect of conflict management through controversial policy settings.
Keywords: Environmental management; Manawatu River Leaders' Forum; Manawatu River